Tahapan Pemberdayaan Masyarakat melalui Program Bank Sampah ‘Gedawang Asri’ Kelurahan Gedawang Kecamatan Tembalang Kota Semarang - Bella, Tiara Khairina; Widowati, Nina (Journal of Public Policy and Management Review, 2022)
Community empowerment through the Gedawang Asri waste Bank program in Gedawang Village is an effort to make waste management can run optimally. The purpose of the study was to analyze the stages of community empowerment through the Gedawang Asri garbage Bank program in Gedawang Village, Banyumanik District, Semarang City and to analyze the factors that influence it. The research method used qualitative descriptive method with data reduction analysis method, data presentation and conclusion. Informants in this study were Chairman of waste Bank, Vice Chairman 1 and 2, Manager, Coordinator of RW using purposive sampling method and customers using accidental sampling. Data collection techniques by way of observation interviews and documentation. The results of the research, the stages of community empowerment is done through 3 stages, namely awareness, exploration and Empowerment. empowerment has not run well because at the stage of awareness there is still a lack of community role in deliberation, socialization that has not been maximized, the absence of a reward and punishment system. At the stage of coordination is still lacking, there is no training related to the marketing of recycled products produced, and finally the stage of Community Empowerment has not maximized the opportunities that exist even though there has been a change in the character of the community in waste management. The factors that encourage this empowerment are infrastructure and cooperation with other parties. The inhibiting factors are the wrong mindset of the community, the lack of customer discipline and the covid - 19 pandemic. The conclusion drawn by the researcher is that the three stages of empowerment in the Gedawang Asri garbage Bank has not run well where there are still driving factors and obstacles that affect the three stages. Suggestions that can be given are the need to resocialize, training for administrators, and product marketing training.